Faktor yang Mempengaruhi Kepuasan Konsumen Rumah Makan Ampera Ramah di Painan dengan Menggunakan Analisis Faktor - Gustrio Zampurnama; Helma Helma (Journal of Mathematics UNP, 2019)
Abstract– Consumer satisfaction is one of the important things that must be considered in the business sector. Indicators that are though to influence consumer satisfaction are product quality, service quality, price, and emotional sense. One of the statistical analysis that commonly  used in analyzing such factors is factor analysis. The data used in this research is primary data obtained from interviews by using questionnaire, where the population is comprised of all Ampera Ramah Restaurants consumers. The samples in this research are about 100 people obtained using accidental sampling methode. Based on the results of this research there are six factors that need to be considered to increase consumer satisfaction i.e 1) taste, menu variation, presentation, and cleanliness, 2) empathy, aesthetics, expression, and innate self, 3) responsiveness and assurance, 4) fairness of prices and affordability, 5) food freshness, shrewdness, and price comparison, and 6) portions and physical evidence. Keywords–Consumer Satisfaction, Restaurants, Factor Analysis.